Substituted epoxides by lithiation of terminal epoxides. - Hodgson, D; Reynolds, N; Coote, S (2004)
Diamine-ligand-assisted direct hydrogen-lithium exchange allows the generation of nonstabilized (H-substituted) oxiranyllithium species and their subsequent trapping by Bu(3)SnCl and carbonyl-based electrophiles. This reaction provides a new concise route to alpha,beta-epoxystannanes and substituted epoxides.